PREVALENCE OF UNCORRECTED REFRACTIVE ERRORS IN ADULTS AGED 30 YEARS AND ABOVE IN A RURAL POPULATION IN PAKISTAN - Abdullah, Ayesha S; Jadoon, Muhammad Zahid; Akram, Mohammad; Awan, Zahid Hussain; Azam, Mohammad; Safdar, Mohammad; Nigar, Mohammad (Journal of Ayub Medical College Abbottabad, 2015)
Background: Uncorrected refractive errors are a leading cause of visual disability globally. This population-based study was done to estimate the prevalence of uncorrected refractive errors in adults aged 30 years and above of village Pawakah, Khyber Pakhtunkhwa (KPK), Pakistan. Methods: It was a cross-sectional survey in which 1000 individuals were included randomly. All the individuals were screened for uncorrected refractive errors and those whose visual acuity (VA) was found to be less than 6/6 were refracted. In whom refraction was found to be unsatisfactory (i.e., a best corrected visual acuity of <6/6) further examination was done to establish the cause for the subnormal vision. Results: A total of 917 subjects participated in the survey (response rate 92%). The prevalence of uncorrected refractive errors was found to be 23.97% among males and 20% among females. The prevalence of visually disabling refractive errors was 6.89% in males and 5.71% in females. The prevalence was seen to increase with age, with maximum prevalence in 51-60 years age group. Hypermetropia (10.14%) was found to be the commonest refractive error followed by Myopia (6.00%) and Astigmatism (5.6%). The prevalence of Presbyopia was 57.5% (60.45% in males and 55.23% in females). Poor affordability was the commonest barrier to the use of spectacles, followed by unawareness. Cataract was the commonest reason for impaired vision after refractive correction. The prevalence of blindness was 1.96% (1.53% in males and 2.28% in females) in this community with cataract as the commonest cause. Conclusions: Despite being the most easily avoidable cause of subnormal vision uncorrected refractive errors still account for a major proportion of the burden of decreased vision in this area. Effective measures for the screening and affordable correction of uncorrected refractive errors need to be incorporated into the health care delivery system. Keywords: Prevalence, Refractive errors, adult population, myopia, hyperopia, astigmatism